Strategi Perencanaan Dan Pengembangan Industri Pariwisata di Kecamatan Panai Hilir, Kabupaten Labuhanbatu - Ajuan Ritonga; Wahyu Haryati Maser; Dian Habibie; Sri Wahyuni (Jurnal Agrisep, 2026)
This study aimed to formulate planning and development strategies for the tourism industry in Panai Hilir District, Labuhanbatu Regency, North Sumatra, using SWOT and QSPM methods. The region holds significant natural and cultural tourism potential, but it has not been optimally developed due to limitations in infrastructure, promotion, and community involvement. This research employed a descriptive approach through the collection of primary and secondary data, which were then analyzed using IFAS, EFAS, SWOT, and QSPM matrices. The SWOT analysis resulted indicate strengths such as natural and cultural richness and community support, and weaknesses including limited facilities and infrastructure. Opportunities included government policies and community support, while threats involve competition from other regions and economic-political conditions. The QSPM analysis produced four main strategies, with the highest priority being the improvement of living standards and community welfare through the tourism sector, followed by infrastructure development, management system enhancement, and capacity building of human resources. These findings are expected to serve as a strategic policy foundation for sustainable tourism development in Panai Hilir and contribute to local economic growth and cultural preservation.